The Effect of Feeding Natural Feed of Daphnia sp. Enriched with Viterna on the Growth of Gourami Fry (Osphronemus gouramy) - Riki Ardiansyah; Andika Putriningtias; Suri Purnama Febri; Muhammad Rizki Shobirin (Universitas Islam Lamongan, 2026)
This study aimed to determine the growth performance of gourami fish (Osphronemus gouramy) fed with Daphnia sp. enriched with Viterna at different doses. The research used an experimental method with four treatments and three replications. The treatments consisted of P1 (0 ml/L as control), P2 (10 ml/L), P3 (20 ml/L), and P4 (30 ml/L) of Viterna enrichment. Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test to determine significant differences among treatments. The results showed that Viterna enrichment significantly affected absolute length growth, absolute weight growth, and daily growth rate (P<0.05), but had no significant effect on survival rate (P>0.05). The highest absolute length growth was observed in P4 (1.79 cm), which was not significantly different from P3 (1.39 cm), while the lowest was found in P1 (0.35 cm). The highest absolute weight growth was also found in P4 (1.91 g), which was not significantly different from P3 (1.64 g), while the lowest was in P1 (0.69 g). The highest daily growth rate was recorded in P4 (3.20%), which was not significantly different from P3 (3.13%), while the lowest was in P1 (2.46%). Based on the results, the enrichment of Daphnia sp. with Viterna at a dose of 20 ml/L (P3) is considered the most effective treatment for improving the growth of gourami fish.